Identification of antioxidant peptides derived from egg‐white protein and its protective effects on H2O2‐induced cell damage. (12th February 2019) - Zhang, Biying; Wang, Huiyu; Wang, Ying; Yu, Yiding; Liu, Jingbo; Liu, Boqun; Zhang, Ting
Summary: To identify novel antioxidant peptides from egg‐white protein and investigate antioxidant mechanism, the hydrolysate of egg‐white protein was purified by ultrafiltration and a Sephadex G‐15 column. The peptides VYLPR, EVYLPR, VEVYLPR and VVEVYLPR were identified from the fraction with the highest antioxidant activity. The Results showed that the peptide VYLPR exhibited the strongest protective effect on HEK‐293 cells. The viability of cells recovered to 97.45 ± 1.98% with pre‐treatment of 20 μm VYLPR. We further investigated antioxidant mechanism. The results showed VYLPR could inhibit lipid peroxidation process, maintain cell membrane integrity, inhibit intracellular LDH activity, reduce MDA content, and improve the activity of antioxidant enzyme T‐SOD and GSH‐Px. This work could help researchers in understanding antioxidant mechanism of peptides and also contribute to developing functional egg‐white product. Abstract : Four peptides were identified from the egg‐white protein. We determined their antioxidant activity in vitro and expolred their protective effect against H2 O2 ‐induced cell damage. The peptide VYLPR exhibited the strongest antioxidant activity. It can inhibit intracellular LDH activity, reduce MDA content, and improve the content of T‐SOD and GSH‐Px in damage cells.